2016
DOI: 10.1016/j.jsat.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Intervention to Improve Primary Care Provider Adherence to Chronic Opioid Therapy Guidelines and Reduce Opioid Misuse: A Cluster Randomized Controlled Trial Protocol

Abstract: Background Prescription opioid misuse is a significant public health problem as well as a patient safety concern. Primary care providers (PCPs) are the leading prescribers of opioids for chronic pain, yet few PCPs follow standard practice guidelines regarding assessment and monitoring. This cluster randomized controlled trial will determine whether four implementation strategies; nurse care management, use of a patient registry, academic detailing, and electronic tools, will increase PCP adherence to chronic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Specifically, we examined the practices, tools and intervention components described in the included articles, and, using the table derived from Adams et al and Lasser et al [Table 3;50, 55], mapped each component to a CCM element that best described that component. We found that all strategies discussed in the included articles aligned closely with at least one CCM element, with the majority of articles addressing a strategy to identify or reduce opioid misuse by addressing the clinical information systems element.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we examined the practices, tools and intervention components described in the included articles, and, using the table derived from Adams et al and Lasser et al [Table 3;50, 55], mapped each component to a CCM element that best described that component. We found that all strategies discussed in the included articles aligned closely with at least one CCM element, with the majority of articles addressing a strategy to identify or reduce opioid misuse by addressing the clinical information systems element.…”
Section: Resultsmentioning
confidence: 99%
“…We recorded information on authorship, article type, publication year, key study findings, clinical setting, GI patient population, and the type of health care practice, tool and intervention to identify and/or reduce opioid misuse on this form. Using a modified version of the categorization approaches previously published [50, 55], a second data charting form was adapted to examine and classify the types of health care practices, tools and interventions presented in the articles according to the key CCM components (Table 3). Information that was organized in the data charting forms was used to collate and report the existing approaches towards identifying and reducing opioid misuse, abuse, or overuse in the GI care setting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lasser et al (2016) article sheds light on common challenges in implementation research. First, patient outcomes, such as reduced mortality rates, are often difficult to power for in a study of this magnitude.…”
Section: Study Protocolsmentioning
confidence: 99%